A C. elegans LSD1 Demethylase Contributes to Germline Immortality by Reprogramming Epigenetic Memory - Katz, David J. (2009)
Recently it has been proposed that di-methylation of histone H3 on lysine 4 (H3K4me2) acts as an epigenetic memory to maintain transcriptional patterns in developing tissues. This model suggests that there may be a requirement to reprogram this modification in the germline to prevent transcriptional memory from being inappropriately transmitted to the next generation. We asked if SPR-5, the C. elegans ortholog of the H3K4me2 demethylase LSD1/KDM1, plays a role in epigenetically reprogramming H3K4me2. We show that spr-5 mutants exhibit progressive sterility over many generations due to defects in oogenesis and spermatogenesis. These defects correlate with a progressive failure to erase H3K4me2 in the primordial germ cells, resulting in the misregulation of spermatogenesis-expressed genes due to the transgenerational accumulation of H3K4me2 at these loci. These results suggest that H3K4me2 can serve as an epigenetic memory and that LSD1/KDM1 demethylases play a critical role in the reprogramming of this memory in the germline, preventing inappropriate epigenetic information from being propagated from one generation to the next.